Adopting a QCA Approach to Investigating the Risks Involved in Megaprojects from Auditing Perspective - Liang Ma; Bing Zhang; Miao Cui; Ruoyu Jin (Discrete Dynamics in Nature and Society)
There is an increase of megaproject construction worldwide. At the same time, risks involved in megaprojects have also become a wide concern. Extending from the macrolevel of qualitative analysis focusing on complexity, politics, and morality, the research conducted the microscopic empirical analysis on twenty-two typical cases by adopting the quality comparative analysis (QCA) from the auditing perspective. Different from the traditional analysis method taking each causation as independent variable, the results in the study revealed that there was complex multiple concurrent causation among eight conditions; additionally, the configuration of those would be divided into six types, among which, the coverage of the three types, namely, project management risk, preliminary and construction risk, and tendering and contract management related risk, was almost eighty percent. Finally, megaproject risks in China were caused by complicated and changeable combination conditions, which would provide a new breakthrough for seeking analyzing megaproject risks through this quantitative analysis method, and indicate the researchers and practitioners to control the megaproject risks from a more systematic way.